Q. 18

Show that</

A =

A2 = =

=

4A = 4

42I = 42

Now,

A2 + 4A – 42I =

=

Hence, =

Now, A2 + 4A – 42I = 0

= A – 1. A . A + 4 A – 1.A – 42 A – 1.I = 0

= IA + 4I – 42A – 1 = 0

= 42A – 1 = A + 4I

= A – 1 =

=

A – 1 =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers